Survey of Oral Manifestation of Covid-19 in Medical Specialties in Sulaimaniyah City Hospitals - Ali M Amin, Sangin; Mohamed Ahmed, Khadija (Diyala Journal of Medicine, 2023)
Background: The coronavirus disease 2019 is a serious infection resulting in a global threat caused by coronavirus 2 (SARS-CoV-2) characterized by different symptoms, ranging from mild flu to severe pneumonia. Objective:To focus on the oral manifestations which could be present in some cases of COVID-19 and to assess the associations between oral health and COVID19. on188 medical specialists in Sulaimaniyah city. The questionnaire was composed of 3 parts; the 1st part included demographic features. The 2nd part was composed of questions concerning the oral hygiene condition of the participants, and the 3rd section encompassed questions about oral complications during infection with COVID-19. Results: Among 188 participants, 92% complained of oral manifestation while being infected with Covid-19 at significant levels. Facial and masticatory muscle pain 27.1%, facial or oral numbness 8%, jaw bones or joint pain 39.9%, changes in buccal mucosa and gingiva 10.1%, bleeding gingivitis 9%, Altered taste sensation 67.6%, altered smell sensation 69.1% and xerostomia 54.8% were highly associated with Covid-19. Conclusion: Some cases of Covid-19 usually present with different oral manifestations. Therefore, oral care monitoring should be enhanced for Covid-19 patients and maintain good oral health.